Rattus feliceus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus feliceus (Thomas, 1920). Ann. Mag. Nat. Hist., 6:423. TYPE LOCALITY: Indonesia, Seram, Mt. Manusela, 6000 ft. DISTRIBUTION: Seram (Molucca Isis., Indonesia). COMMENT: Formerly included in ruber, sensu Laurie and Hill, 1954: 110 (see praetor); see Musser, 1981, Bull. Am. Mus. Nat. Hist., 169(2): 168, who considered feliceus a distinct species. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 549, DOI: 10.5281/zenodo.7353037